Analisis Kompetensi Pedagogik Guru Dalam Pelaksanaan Kurikulum 2013 Pada Mata Pelajaran Ekonomi Di Sma Muhammadiyah 1 Surakarta - Nilawati, Fitri; , Suranto, S.Pd., M.Pd (2017)
This study aims to determine the level of understanding of the pedagogical competence of economic teachers in SMA Muhammadiyah 1 Surakarta in the implementation of the curriculum 2013. Research subjects are economics teachers and vice principals curriculum. Data collection techniques used are interviews, observations, and documents. Data are analyzed through data collection steps, presentation, data reduction and conclusion. Technique examination of data validity is done by trianggulasi technique and source triangulation. The result of the research shows the fulfillment of pedagogic competence of teacher for teacher understanding indicator toward student, planning and implementation of learning, implementation of learning that is educational and conducive, evaluation of learning process and student development to actualize various potency have good criteria. This shows that economic teachers meet all pedagogical competency indicators in line with the demands of the 2013 curriculum. In addition, the results of interviews show that economics teachers accept government policies to change the curriculum into the 2013 curriculum and are willing to implement the 2013 curriculum. Because it is perceived that teachers' Changes are needed. With this curriculum change the teacher can improve the soft skill and hard skill of students covering attitude aspect, knowledge and skill so that can make education better again.